Association Between Vertebral Artery Stiffness and Idiopathic Subjective Tinnitus: A Prospective Study - Ismail Aytac; Alper Yazici; Orhan Tunc; Rauf Gul; Yusuf Inanc; Koray Tumuklu (Applied Sciences)
Objectives: Tinnitus, defined as the perception of sound without an external stimulus, is a complex condition with unclear etiology. Emerging evidence suggests a link between vascular dysfunction, particularly arterial stiffness, and tinnitus. This study aimed to evaluate vertebral artery stiffness in patients with idiopathic subjective tinnitus and assess the utility of Doppler ultrasonography as a non-invasive diagnostic tool. Materials and Methods: In this prospective study, 31 patients with idiopathic tinnitus (11 males, 20 females; mean age: 50.42 ± 9.64 years) and 24 healthy controls (12 males, 12 females; mean age: 39.67 ± 10.63 years) underwent comprehensive clinical evaluations, including pure tone audiometry, blood tests, and vertebrobasilar Doppler ultrasonography. Vertebral artery stiffness index (VAS), resistive index (RI), and pulsatility index (PI) were measured bilaterally. Results: A total of 31 patients with idiopathic subjective tinnitus and 24 healthy controls were evaluated. The mean age was significantly higher in the tinnitus group compared to controls (50.42 ± 9.64 vs. 39.67 ± 10.63 years, p < 0.001). Lipid profile analysis revealed significantly higher levels of total cholesterol (193.6 ± 47.28 vs. 167.5 ± 28.99 mg/dL, p = 0.021), LDL (149.4 ± 37.9 vs. 106.1 ± 10.7 mg/dL, p < 0.005), and triglycerides (202.2 ± 83.5 vs. 148.6 ± 26.4 mg/dL, p < 0.005) in tinnitus patients. Doppler ultrasonography demonstrated significantly higher vertebral artery stiffness values in the tinnitus group (left: 2.87 ± 0.72 vs. 2.12 ± 0.22; right: 2.99 ± 0.77 vs. 2.14 ± 0.5; both p < 0.005). Similarly, pulsatility index (PI) was significantly elevated in patients compared to controls (left: 2.45 ± 1.2 vs. 1.2 ± 0.43; right: 2.49 ± 1.02 vs. 1.19 ± 0.42; both p < 0.005). No significant differences were observed in resistive index (RI) or vertebral artery diameters between groups. Among tinnitus patients, PI and VAS were significantly higher on the side corresponding to reported tinnitus symptoms (p < 0.05), suggesting a lateralized vascular contribution. Conclusions: The findings suggested a potential relationship between idiopathic subjective tinnitus and vertebral artery stiffness. We demonstrated the utility of Doppler ultrasonography, a cost-effective and non-invasive imaging modality, for evaluating vascular parameters in tinnitus patients, paving the way for broader clinical applications. By uncovering a significant association between vertebral artery stiffness and tinnitus, our findings suggest that vascular health assessments could enhance diagnostic and therapeutic strategies for tinnitus management.